Factors influencing the payment of zakat on employment income in Segamat, Johor / Muhammad Nazhan Azlimi - Azlimi, Muhammad Nazhan (Faculty of Business and Management, 2019)
Zakat is the fourth fundamental pillar of Islam. Zakat is a payment that is obligate to all Muslims. Literally zakat means purify and growth. There are many types of zakat that are obligated to Muslim people but this research only want to focus on zakat on employment income. Zakat on employment income is payment that been make after deducting the basic expenditure, exceed the nisab amount and based on lunar year. Nowadays, there are certain Muslim workers in this country that have exceeded sources and income does not make a payment ofzakat on employment income. The result from this research can be use in order to improve the performance of the Muslim workers in making the payment of zakat in employment income in Malaysia in general and Segamat particularly. This research aims to analyze the factors influencing the payment ofzakat on employment income in Segamat, Johor. The main objective of this research is wanted to analyze the factor influencing the payment ofzakat on employment income in Segamat, Johor. There are two variables involve in this research which are independent variable include knowledge, income and self- awareness and dependent variable include payment of zakat on employment income. There are 150 sets of questionnaire had been distributed to the respondents in Segamat area in order to collect the data. Lastly, the SPSS 2.2 is used to analyze the data collected for the purpose of analysis.